2014
DOI: 10.1530/endoabs.34.p315
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of Nigerian honey on sperm indices and testis in sucrose-fed rat

Abstract: The reproductive capacity of the male rat is higher than that of man therefore, the decrease in sperm quality observed in the HSS-fed rats may be enough to alter fertility among male humans, thus contributing to the alarming incidence of male infertility. Nigerian honey conversely is an alternative sweetener and exhibits protective function against reproductive dysfunction via HS-feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Another study on applied to rats showed that persistent consumption of Nigerian honey (i.e 5 ml/kg and 7.5 ml/kg body weight) had a negative impact on sperm parameters and fertility potential of male Wistar rats (Dare, Igbigbi, & Avwioro, 2013). Oyelowo et al (2014) also studied the protective potential of Nigerian honey on sperm indices and testis in sucrose-fed rats. They found that the high sucrose diet had adverse impacts on male reproductive function Composition, nutritional, antioxidant of honey while honey feeding showed a protective impact on reproductive dysfunction.…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…Another study on applied to rats showed that persistent consumption of Nigerian honey (i.e 5 ml/kg and 7.5 ml/kg body weight) had a negative impact on sperm parameters and fertility potential of male Wistar rats (Dare, Igbigbi, & Avwioro, 2013). Oyelowo et al (2014) also studied the protective potential of Nigerian honey on sperm indices and testis in sucrose-fed rats. They found that the high sucrose diet had adverse impacts on male reproductive function Composition, nutritional, antioxidant of honey while honey feeding showed a protective impact on reproductive dysfunction.…”
Section: Anti-inflammatorymentioning
confidence: 99%